O2.6. A TWO-YEAR LONGITUDINAL EVALUATION OF DIFFUSION MEASURES OF EXTRACELLULAR FREE WATER IN A NON-HUMAN PRIMATE MODEL OF MATERNAL IMMUNE ACTIVATION – EXPLORING NEUROIMMUNE MECHANISMS OF PSYCHIATRIC DISORDERS. (9th April 2019) - Lesh, Tyler; Iosif, Ana-Maria; Tanase, Costin; Vlasova, Roza; Styner, Martin; Van De Water, Judy; Maddock, Richard; Bennett, Jeffrey; Amaral, David; Bauman, Melissa; Carter, Cameron
Abstract: Background: Evidence has been accumulating for an immune-based component of psychiatric disorder etiology, particularly schizophrenia. One of the first indications of such a link comes from early epidemiological studies, which found an increased incidence of schizophrenia in offspring of mothers who had an infection during pregnancy. Recent work has identified genetic links to the major histocompatibility complex, pro-inflammatory cytokine elevations, as well as mixed evidence of microglial activation. While these findings provide strong evidence of an immune component, human studies are inherently limited by the heterogeneity of the sample and inability to make strong inferences about causality. Consequently, we have developed a non-human primate (NHP) model of maternal immune activation (MIA) using a modified form of the viral mimic polyIC (polyICLC) to test the hypothesis that maternal immune response contributes to changes in the developing brain and behavior of NHP offspring. Specifically, this study examines the effect of MIA on a promising biomarker of neuroinflammation in vivo--extracellular free water--a diffusion magnetic resonance imaging measure obtained with a multi-shell acquisition. We sought to test the hypothesis that offspring of pregnant monkeys who received polyICLC injections would show increased extracellular free water compared to control offspring. Methods: Fourteen pregnant rhesus monkeys (Macaca mulatta) received polyICLC at the end of the first trimester and 10 pregnant monkeys received saline injections. An additional four offspring were added to reach target enrollment of 14 control animals. The offspring from both groups (all of whom were male) underwent a diffusion MRI scan on a 3 Tesla Siemens Skyra scanner in which multiple b-value shells were acquired to improve estimation of extracellular free water. Data were collected when the offspring were 1, 6, 12, and 24 months of age. Diffusion images were nonlinearly aligned to individual subject MPRAGE scans, which were segmented and parcellated into regions of interest using multi-atlas techniques. For this preliminary analysis, frontal, cingulate, and temporo-limbic regions were selected as a priori ROIs in addition to whole-brain gray and white matter. Group differences were assessed using linear mixed-effect models implemented in SAS. Results: No significant group by time interactions were identified, with groups displaying parallel trajectories from 6 to 24 months. A significant main effect of group was identified in both white (p<.05) and gray (p<.001) cingulate cortex free water, with MIA-exposed offspring showing higher free water. Similar trends were also identified in prefrontal white matter free water (p=.07) and whole-brain white (p=.11) and gray matter free water (p=.07). A significant main effect of time was also identified across all regions of interest with higher free water present in both groups at 24 months compared to baseline. Discussion: These data suggest that extracellular free water values are increased in MIA-exposed offspring, particularly in the cingulate cortex. More global whole-brain free water group differences, however, did not reach statistical significance, which may indicate some regional specificity to these changes early in development. Nonetheless, the NHP MIA model complements the human schizophrenia literature, in which extracellular free water increases have been repeatedly identified. Ultimately, these data provide validation of the clinical relevance of the NHP MIA model and improve our understanding of neuroimmune mechanisms in the development of psychiatric disorders, particularly schizophrenia.